Angiotensin-converting-enzyme insertion/deletion polymorphism, ACE activity, and COVID-19: A rather controversial hypothesis. A case-control study - Papadopoulou, A.; Fragkou,P.C.; Maratou, E.; Dimopoulou,D.; Kominakis,A.; Kokkinopoulou, I.; Kroupis, C.; Nikolaidou, A.; Antonakos, G.; Papaevangelou, V.; Armaganidis, A.; Tsantes,A.; et al. (J.Med.Virol., 2022)
Accumulating data has shown a contribution of the renin-angiotensin system in COVID-19 pathogenesis. The role of angiotensin-converting enzyme (ACE) insertion (I)/deletion (D) polymorphism as a risk factor in developing COVID-19 disease comes from epidemiological data and is controversially discussed. We conducted a retrospective case-control study and assessed the impact of ACE I/D genotype in COVID-19 disease prevalence and severity. In 81 COVID-19 patients explicitly characterized and 316 controls, recruited during the first wave of COVID-19 pandemic, ACE I/D genotype, and ACE activity were determined. A generalized linear model was used and Poisson regression analysis estimated the risk ratios (RRs) of alleles and genotypes for disease severity. DD patients had almost 2.0-fold increased risk (RR: 1.886, confidence limit [CL] 95%: 1.266-2.810, p = 0.0018) of developing a more severe disease when contrasted to ID and II individuals, as did D allele carriers compared to I carriers (RR: 1.372; CL 95%: 1.051-1.791; p = 0.0201). ACE activity (expressed as arbitrary units, AU/L) was lower in patients (3.62 +/- 0.26) than in controls (4.65 +/- 0.13) (p < 0.0001), and this reduction was observed mainly among DD patients compared to DD controls (3.97 +/- 0.29 vs. 5.38 +/- 0.21; p = 0.0014). Our results demonstrate that ACE DD genotype may predispose to COVID-19 increased disease severity via a mechanism associated, at least in part, with the significant fall in their ACE activity. Our findings suggest a more complex pattern of synergy between this polymorphism and ACE activity in COVID-19 patients compared to healthy individuals and set the grounds for large-scale studies assessing ACE genotype-based optimized therapies with ACE inhibitors and angiotensin receptor blockers
IS - 1096-9071 (Electronic) IS - 0146-6615 (Print) IS - 0146-6615 (Linking) LA - eng PT - Journal Article RN - EC 3.4.15.1 (ACE protein, human) RN - EC 3.4.15.1 (Peptidyl-Dipeptidase A) SB - IM
Keywords: Alleles; Case-Control Studies; Covid-19; genetics; Humans; INDEL Mutation; metabolism; Pandemics; Peptidyl-Dipeptidase A; physiopathology; Polymorphism,Genetic; Retrospective Studies; Severity of Illness Index